The Interactive Effect of Communication Satisfaction and Cultural Dimensions on Organizational Commitment: A Case of Four Universities in Yemen - Al-Neshmi, Murad Mohammed Abdullah (Universiti Utara Malaysia, 2011)
This study investigates the interactive effect of communication satisfaction and cultural dimensions on organizational commitment. The study also aims at identifying the moderating effects of national culture on the communication satisfaction-organizational commitment relationship. To achieve the objectives of the study, quantitative data were collected from academic staff working in four universities in Yemen. Stratified random sampling was employed in the sample selection and a total of 362 academic staff participated in a survey by returning the study questionnaire distributed to them. The study participants were from five different nationalities i.e. Egyptians, Iraqis, Indians, Malaysians, and Yemenis. Statistical analysis used for analyzing the data of the study included descriptive statistics, ANOVA, Pearson Correlation, Multiple Regression, and hierarchical multiple regression. The findings of the study indicated that the academic staffs level of satisfaction with communication practices has ranged from low to moderate. The academic staffs organizational commitment was also moderate. The findings also showed many significant differences between Yemeni and non-Yemeni academic staff in the level of communication satisfaction with regard to the nine dimensions of communication satisfaction. Results of correlation analysis indicated significant positive bivariate relationships between communication satisfaction dimensions and the three dimensions of organizational commitment. The multiple regression analysis showed that organizational perspective; personal feedback; media quality; and top management communication are the communication satisfaction dimensions that very much predict the affective commitment, while media quality was the only dimension that predicts both continuance and normative commitment. The results of the hierarchical multiple regressions indicated that national culture dimensions moderate the relationship between communication satisfaction dimensions and organizational commitment dimensions. The study has indicated that the relationship between organizational commitment and communication satisfaction which is significantly positive is affected by national culture. The findings of this study provide a valuable knowledge to universities and organizations which have multinational staff working in them and guide these universities to understand the significance and the importance of communication satisfaction for their staff to be highly committed in order to perform well. The findings also help the management of these universities to develop strategies for elevating their staffs communication satisfaction level in order to provide a healthy academic environment and to reach a high-quality outcome.